2020
DOI: 10.1186/s40478-020-00912-x
|View full text |Cite
|
Sign up to set email alerts
|

KLF4K409Q–mutated meningiomas show enhanced hypoxia signaling and respond to mTORC1 inhibitor treatment

Abstract: Meningioma represents the most common primary brain tumor in adults. Recently several non-NF2 mutations in meningioma have been identified and correlated with certain pathological subtypes, locations and clinical observations. Alterations of cellular pathways due to these mutations, however, have largely remained elusive. Here we report that the Krueppel like factor 4 (KLF4)-K409Q mutation in skull base meningiomas triggers a distinct tumor phenotype. Transcriptomic analysis of 17 meningioma samples revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 44 publications
1
20
0
3
Order By: Relevance
“…TRAF7 mutations are present in approximately 25% of sporadic meningiomas, and studies have revealed they are mutually exclusive from NF2 mutant tumors, yet larger studies are need to confirm exclusivity of TRAF7 mutant tumors. TRAF7 mutations also present with mutations in AKT1 or KLF4, especially those KLF4 mutations as a result of the recurrent K409Q mutation [33]. Tumors with mutations in both TRAF7 and KLF4 are most often found in secretory meningiomas with TRAF7 mutant tumors having a predilection for the anterior skull base [24].…”
Section: Traf7mentioning
confidence: 99%
“…TRAF7 mutations are present in approximately 25% of sporadic meningiomas, and studies have revealed they are mutually exclusive from NF2 mutant tumors, yet larger studies are need to confirm exclusivity of TRAF7 mutant tumors. TRAF7 mutations also present with mutations in AKT1 or KLF4, especially those KLF4 mutations as a result of the recurrent K409Q mutation [33]. Tumors with mutations in both TRAF7 and KLF4 are most often found in secretory meningiomas with TRAF7 mutant tumors having a predilection for the anterior skull base [24].…”
Section: Traf7mentioning
confidence: 99%
“…DNA extracted from FFPE tissue was processed using standard procedures as previously described [ 42 ]. We analyzed all meningiomas for known hotspot mutations in the genes SMO (L412F and W535L) [ 4 ], AKT1 (E17K) [ 42 ], and KLF4 (K409Q) [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…HEK293T cells (DSMZ, Braunschweig) were transfected using FuGene® HD transfection reagent (Promega, Mannheim, Germany) with pLV[Exp]‐Bsd‐EF1A > hAKT1[NM_005163.2] and pLV[Exp]‐Bsd‐EF1A > [hAKT1[NM_005163.2]*(E17K) (VectorBuilder) in combination with lentiviral packaging plasmid mix pC‐Pack 2 (Cellecta) as reported 30 . Both plasmids contain the same lentiviral vector backbone.…”
Section: Methodsmentioning
confidence: 99%
“…The head skin was cut longitudinally. A single hole was drilled 1.5 mm anterior of the bregma and 2 mm on the right side from the sagittal suture and 0.5 × 10 5 transfected IOMM‐Lee cells ( AKT1 wt or AKT1 E17K ) in 0.5‐μl PBS were deposited above the skull base bone (about 7.5 mm in depth) 30 …”
Section: Methodsmentioning
confidence: 99%